The influence of biophilic design to learning ability in library environment: A systematic review / Nur Afizah Mohd Khair, Azizah Md Ajis and Siti Rasidah Md Sakip - Mohd Khair, Nur Afizah; Md Ajis, Azizah; Md Sakip, Siti Rasidah (2022)
The library is one of the important infrastructural facilities for university students to enhance their learning experience, providing various materials, equipment, gadgets, and spaces. A sustainable environmental design library could not only improve the quality of life and learning outcomes of university students but also help to improve the learning ability and emotion during the process of learning. While the impact of environmental design on people's ability and emotion has been extensively researched in some contexts, such as offices, hospitals, and elementary schools, the research on biophilic design in urban post-secondary educational environments has limited resources. For this reason, this paper thoroughly reviews literature that explores biophilic design as a strategy to increase students' learning ability in the library environment. The study investigates the design strategies, through a systematic literature review that includes the process of appraising the literature from a related fields, data extraction based on several keywords, analysis and synthesis and finally reporting the results. The results revealed a wide range of benefits, from the improvement of the learning environment to the promotion of pro-environmental behaviour toward learning ability and emotion. This study is expected could beneficial to designers, student researchers, academic instructors, building occupants, and sustainable development goals.